Transforming Export Competitiveness: Technological Upgradation and Digitalization in the Indian HVAC Industry - Pol, Akash M (Digital Repository of Theses, 2026)
Export competitiveness in the manufacturing industry is being increasingly influenced by technological sophistication and digital preparedness, especially in emerging economies such as India. The Indian Heating, Ventilation, and Air Conditioning (HVAC) industry has witnessed growing at a fast rate and now holds a large space in the global supply chain. However, little empirical research has looked at the effect of technological upgradation and digitalization on competitiveness in exports or their interaction. This study fills this gap by examining the role of technological development and digital transformation in the export competitiveness of the Indian HVAC industry and also identifies the key barriers and enablers of technological transformation. A mixed methods research design was used. The quantitative component consisted of the panel data regression analysis of 51 low and middle-income countries, including India, with the 2000-2022 time period. Diagnostic tests supported that the best specification was the Random Effects Model. While the qualitative component was conducted through semi-structured interviews with key stakeholders of the Indian HVAC market which included manufacturers, exporters, policymakers, and technology experts. The qualitative data were analyzed in terms of firm-level experiences through thematic analysis. The quantitative results indicate a strong and positive statistically significant correlation between technological upgradation and export competitiveness, which implies increasing levels of higher technological advancement in favour of export performance. In contrast, the existence of digital infrastructure alone is not found to have statistically significant direct impact, raising the assumption that digitalization only contributes to competitiveness when combined with technological capabilities and support organizational systems. The qualitative findings provide support for these findings that automation, advanced manufacturing and energy efficient technologies enhance product quality, compliance with international standards and export readiness. Digital tools further boost coordination, transparency and engagement with the global markets. Human capital preparedness, leadership commitment, financial capacity, and organizational readiness were found to be key determinants for successful technology adoption. The research finds that the emergence of export competitiveness in the Indian HVAC industry with the result of synergy between technology upgradation, digitalization and organizational capability with technology being the driver and digitalization serving as strategic enabler.